The Effectiveness of Growth Mindset-Based Role Play in Improving Early Childhood Self-Confidence - Mutmaina Hani; Durrotunnisa Durrotunnisa; Sita Awalunisah; Andi Agusniantih; Razkia Razkia; Vita Marcella; Agis Agis (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aims to determine the effectiveness of the role-playing method based on a growth mindset in improving early childhood self-confidence in Group A of TK Kemala Bhayangkari 16 Palu. This research employed a quasi-experimental approach with a one-group pretest-posttest design. The subjects of this study were 14 children aged 4–5 years. Data were collected through observation based on three indicators: courage to perform and participate, ability to express opinions, and independence and perseverance. The results showed that in the pretest phase, most children were in the